E-PORTFOLIO BASED LEARNING: STUDENT RESPONSE IN LEARNING SPEAKING: STUDENT RESPONSE IN LEARNING SPEAKING - Dedin Aliyudin; Kusrin Kusrin; Yousef Bani Ahmad (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
The present study aimed to investigate the response of E-portfolio on EFL students’ speaking classroom. This study conducted to examines whether e-portfolio has good effect on improving student speaking skill. This study conducted at one of the junior high school in Bandung in the academic year 2019/2020. Seven students participated in this study. The type of this study was qualitative research and its design was a case study. The data obtained through observation, interview, and documentation. The findings of the research showed that E-portfolio has a positive response from the students. It was proven by the result of the data that the students helped by using E-portfolio as a speaking learning media. In addition, the result of this study indicates that E-portfolio is an interesting learning media to help students on their listening skills.